THE INFLUENCE OF SERVICE QUALITY AND PRICE PERSEPTION FOR LOYALITY OF THE CUSTUMERs AT WAROENG STEAK AND SHAKE SISINGAMANGARAJA - Sonia Mayuni Ritonga; Nurain Harahap; Julianto Hutasuhut (Jurnal Ekonomi, 2023)
This research used quantitative method. The purpose of this research is to analysis The Influence Of Service Quality And Price Perseption For Loyality Of The Custumor At Waroeng Steak And Shake Sisingamangaraja. The riset’s popuation is the custumor of waroeng steak and shake sisingamangaraja 95 people in number. This research, sample was taken by using saturated sampling technique. All of the customers were taken to become object of research 95 people in total. The analysis technique used is multiple linear regression analysis using the SPSS 25.00 version program. Service Quality and price perception give positive and significant influence for Loyality of the customer at Waroeng Steak And Shake Sisingamangaraja. Adjusted R Square from the analysis of the coefficient of determination of 0.622 means that customer loyalty can be explained by service quality variables and price perceptions of 62.2%, while the remaining 37.8% can be explained by other variables not examined in this research.